Comparative Evaluation of Usability between QWERTY-Based Arabic and Non-QWERTY-Based Arabic Keyboard Layout: Empirical Evidence - Aknuranda, Ismiarta; Syawli, Almira; Setiawan, Budi Darma (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
QWERTY-based Arabic keyboard layouts have been in existence in order to assist QWERTY users in Arabic typing. However, there was lack of empirical evidence presenting the comparative usability of this layout and the common non-QWERTY-based Arabic keyboard layout. This study examined the usability of a QWERTY-based Arabic keyboard layout (QB) and the common non-QWERTY-based Arabic keyboard layout (NQB) from the perspective of QWERTY users, and compared the evaluation results between the two layouts. After experiments using within-subjects and between-subjects designs, the results showed that QB is significantly better in efficiency and learnability than NQB. QB also enabled more effective typing in almost all experiment designs, except in one between-subjects study. The relatively short interaction time of participants’ first encounter with Arabic keyboards possibly caused this exception. Most participants subjectively preferred QB to NQB in their overall usability.